VALIDATION OF EQUATIONS OF SKINFOLD THICKNESS FOR FAT MASS ESTIMATION IN HIV/AIDS SUBJECTS: A COMPARISON OF DUAL ENERGY X-RAY ABSORPTIOMETRY AND COMPUTED TOMOGRAPHY OF ABDOMEN - Alex Antonio Florindo; Maria do Rosario Dias de Oliveira Latorre; Aurélio Borelli; Manoel de Souza Rocha; Aluisio Augusto Cotrim Segurado (Revista Brasileira de Atividade Física e Saúde)
The objective of the present study was to develope and to validate equations based on skinfold thickness for the estimation of percent body fat (%BF) in HIV/AIDS subjects using dual energy X-ray absorptiometry (DEXA) and computed tomography of abdomen (CTA) as the gold standards. The sample included 15 adult Brazilian HIV/AIDS subjects (10 men and 5 women). Mean age was 36.9 years (SD 8.2) and mean %BF by DEXA was 18.2 (SD 9.5). The estimation of %BF was done using linear regression models, and the independent variables were the sum of one to seven skinfold thickness. The skinfold thickness was compared with DEXA and CTA. The Durnin & Womersley equation was also tested. The best equation for males was [%BF = 3.385 + 0.279 * (axillary + subscapular); r2=0.83] and for females was [%BF = -24.323 + 0.736 * (suprailiac + abdominal + medial calf); r2=0.81]. The total error of the estimate of %BF in HIV/AIDS was 3.5% for males and females in the comparison with DEXA. The HIV/AIDS equation complied with all the validation criteria. We recommended this equation to be tested in larger samples for estimating %BF among HIV/AIDS subjects.